Barriers, Benefits, and Contraceptive Stages of Change in Adolescents Mothers Postpartum: A Systematic Review - Martínes-Escalante, Richard Francisco; Caudillo Ortega, Lucía; Benavides-Torres, Raquel Alicia (Horizonte Sanitario, 2024)
Objective: To identify available evidence on the perceived benefits and barriers faced by adolescent mothers in the postpartum stage and to determine the stage of change regarding the use of contraceptive methods.Materials and Methods: A search for scientific studies was conducted from August to December 2022, with an extension of the search from September to November 2023, in English and Spanish. Following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guide, in the PubMed, SCOPUS, EbscoHost and LILACS databases, the keywords used were "Postpartum", "contraceptive methods", "pregnancy", "adolescent", "births", "stages of change", "benefits" and "barriers" using Boolean operators "AND" and "OR". The review question was elaborated by setting Patient, Concept and Context. To assess the quality of the studies, the checklist proposed by the Joanna Briggs Institute was used. Results: A total of 268 studies were identified; after screening and review, 11 studies were included. The majority of these studies were conducted in the United States and Brazil, with sample sizes ranging from 64 to 5480 adolescents in the postpartum stage. Reported benefits include the desire to avoid a new pregnancy, satisfaction with the method, access to contraception, and community approval. The most common barriers in the studies were the side effects of contraceptive methods and the desire for a new pregnancy. The stages of change where most adolescents are found are contemplation and action. Conclusions: Adolescent mothers in the postpartum stage are at a crucial moment to choose and start using a contraceptive method, provided they perceive a greater number of benefits than barriers. Key words: Contraceptive agents; Postpartum period; Adolescent mothers; Transtheoretical Model.